Edukasi Scale-Up UMKM Dan Pemilihan Investasi Era Endemi Covid-19 - Maulidizen, Ahmad; Winanto, Sujoko; Amriatus Safaah; Thoriq, Muhammad Rafi (Jurnal Pengabdian Kepada Masyarakat, 2022)
The COVID-19 pandemic has impacted all sectors of the Indonesian economy. Many MSME actors close their businesses because of the declining interest in buying people. This activity aims to provide helpful information so that MSME actors receive stimulus funds to re-run existing businesses. They conducted this activity online through a zoom meeting attended by MSME actors from various sectors. Therefore, providing recommendations for MSMEs to sell their products through e-commerce and promote them through digital marketing as a marketing strategy to survive the pandemic. In addition, MSMEs also need to optimize marketing relationships with customers through customer relationship marketing to create loyal customers. Loyal customers have the potential to make repeat purchases and recommend products to other potential customers. By implementing this strategy, it is hoped that MSME businesses can continue to survive and have a positive impact on society and the economy Empowerment of Waqf through the Agricultural Sector as an Effort for Family Economic Resilience